Injury frequency and most common injuries among professional football players in Croatia - Grgic, M.; Šklempe Kokic, I. (10th International scientific conference on kinesiology. Book of abstracts, 2024)
Football is the most popular sport worldwide. In recent times, football players have been subjected to significantly higher training loads and competitive matches, resulting in an increase in the number of injuries. The aim of this research was to determine the frequency and most common sports injuries among professional football players in the Republic of Croatia.The study involved 440 participants, professional football players in Croatia, including Croatian national team players. All participants were personally provided with an online questionnaire via online platform, which they were required to complete according to instructions. Data analysis aimed to analyze basic descriptive parameters. The results showed that 91% of the participants had an injury that kept them off the sports field for 2 weeks or longer. Sixty-two percent of the participants had a muscle injury that required treatment for more than 2 weeks, and 75% had a joint injury. Joint injuries were more common among participants in this study than muscle injuries. The most common joint injury was ankle joint injury, and the most common muscle injury was damage to the m. suadriceps femoris in addition to adductors muscles. These results suggest that almost every professional football player experiences an injury during their career that prevents them from training normally for 2 or more weeks. Additionally, the results of this study can be used for preventive activities within the training process.